Composite dressing with sequential response and function synergistic effect as well as preparation and application of composite dressing

By utilizing the cascade catalysis and photothermal response mechanism of the double-layer composite dressing, the problem of mismatch between microenvironment regulation and drug release in diabetic wound dressings was solved, realizing full-process intervention from basic support to advanced repair, and significantly improving the healing efficiency and safety of diabetic wounds.

CN120815205AActive Publication Date: 2025-10-21DONGHUA UNIV +1

Patent Information

Application Number
CN202511341295.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-10-21
Estimated Expiration
2045-09-19

AI Technical Summary

Technical Problem

Existing diabetic wound dressings have limited ability to regulate the microenvironment, mismatched drug release timing, and low efficiency in promoting angiogenesis, resulting in treatment effects that fail to meet clinical needs.

Method used

The dressing employs a dual-layer composite structure, comprising a PVA-GOx-MnO2 hydrogel layer and a temperature-sensitive micro/nanofiber membrane layer. It improves the local microenvironment through a cascade catalytic reaction and triggers drug release under near-infrared light irradiation, thereby achieving a synergistic effect.

Benefits of technology

It significantly improves the healing efficiency and treatment safety of diabetic wounds by actively regulating the microenvironment and precisely releasing drugs, achieving full-process intervention from basic support to advanced repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120815205A_ABST
    Figure CN120815205A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and relates to a composite dressing with sequential response and functional synergy as well as preparation and application thereof, the composite dressing is of a double-layer composite structure, and comprises a PVA-GOx-MnO2 hydrogel layer and a temperature-sensitive micro-nanofiber membrane layer; the PVA-GOx-MnO2 hydrogel precursor solution is prepared by adding glucose oxidase and MnO2 nano particles into a polyvinyl alcohol solution under the condition of ice bath, and the PVA-GOx-MnO2 hydrogel precursor solution is prepared by adding glucose oxidase and MnO2 nano particles into the polyvinyl alcohol solution; the preparation method comprises the following steps: placing the temperature-sensitive micro-nano fiber membrane on a PVA-GOx-MnO2 hydrogel precursor solution or immersing the temperature-sensitive micro-nano fiber membrane in the PVA-GOx-MnO2 hydrogel precursor solution, carrying out crosslinking treatment, and demolding to obtain the composite dressing. The application is as follows: the material is used as a diabetic chronic wound repair material. The problems that an existing diabetes wound dressing is weak in microenvironment regulation and control capacity and the drug release time is not matched are solved; the preparation method is simple; the healing efficiency and the treatment safety of diabetic wounds are remarkably improved during application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials, and relates to a composite dressing with temporal response and functional synergy, as well as preparation and application thereof. Background Art

[0002] Diabetes is a metabolic disease characterized by chronic hyperglycemia. Its incidence has continued to rise in recent years due to lifestyle changes and an aging population. According to the International Diabetes Federation (IDF), the number of people with diabetes worldwide reached 643 million by 2025 and is projected to exceed 800 million by 2050. Chronic diabetic wounds, such as diabetic foot ulcers, are a serious complication of diabetes and have become a major clinical problem leading to amputation and death. Diabetic wounds are characterized by a long healing period, susceptibility to infection, and high recurrence rates. These wounds are primarily caused by factors such as a local high-glycemic environment, disrupted inflammatory responses, enhanced oxidative stress, and decreased angiogenesis. This adverse microenvironment significantly inhibits cell proliferation, migration, and neovascularization, severely impacting tissue repair processes and making traditional treatments ineffective. Currently, commonly used clinical treatments include debridement, anti-infective therapy, negative pressure drainage, and topical dressings and medications. However, existing treatment methods generally have the following problems: lack of systematic regulation of the microenvironment; topical drugs are easily washed away by exudates and difficult to maintain effective concentrations for a long time; the timing of drug release does not match the wound repair stage, resulting in low angiogenesis efficiency and limited therapeutic effect.

[0003] In recent years, hydrogel dressings have been widely used in the field of chronic wound management due to their good water retention, biocompatibility and ability to load a variety of active ingredients. Through structural design, hydrogels can achieve sustained-release, controlled-release and even responsive drug delivery, showing great advantages in promoting wound healing. However, existing hydrogel dressings still have some significant limitations: most dressings have a single function and lack effective intervention in the complex microenvironment of diabetic wounds, such as high sugar, hypoxia, and oxidative stress; at the same time, the drug release mechanism is mostly passive diffusion, which makes it difficult to dynamically and accurately regulate the timing according to the stage needs of wound repair, resulting in low drug utilization and unstable treatment effects.

[0004] To address these issues, existing technologies have explored various approaches. For example, multifunctional hydrogel dressings disclosed in patents CN118717902A, CN117815438A, and CN117084970A improve the microenvironment of diabetic wounds by integrating multiple functional modules, including antioxidant, anti-inflammatory, and repair-promoting ones. However, these dressings lack sequential control over their multiple functions, making it impossible to achieve a progressive intervention approach of "regulation first, then treatment."

[0005] Patents such as CN120025564A and CN119606872A focus on developing responsive drug release systems, leveraging microenvironmental stimuli such as pH, ROS, and temperature to achieve controlled drug release. While these technologies can achieve "dynamic regulation," they are essentially passive responses to existing microenvironmental changes and do not actively improve the microenvironment.

[0006] In summary, although existing dressings have made certain progress in the treatment of diabetic chronic wounds, they still generally face problems such as limited ability to regulate the local microenvironment, mismatched drug release timing, and low efficiency in promoting angiogenesis, resulting in the overall treatment effect being difficult to meet clinical needs.

[0007] Therefore, it is of great significance to study a composite dressing with temporal response and functional synergy and its preparation and application to solve the problems existing in the existing technology. Summary of the Invention

[0008] The purpose of the present invention is to solve the problems existing in the prior art and provide a composite dressing with temporal response and functional synergy, as well as its preparation and application.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] A composite dressing with temporal response and functional synergy, which is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a temperature-sensitive micro-nano fiber membrane layer;

[0011] The PVA-GOx-MnO2 hydrogel is prepared by cross-linking a PVA-GOx-MnO2 hydrogel precursor solution. This solution is prepared by adding glucose oxidase (GOx) and MnO2 nanoparticles to a polyvinyl alcohol (PVA) solution in an ice bath. The main function of PVA is to form a three-dimensional network structure within the hydrogel to support the GOx and MnO2 nanoparticles and maintain their catalytic activity.

[0012] The thermosensitive micro-nanofiber membrane is a thermosensitive micro-nanofiber membrane loaded with angiogenesis-promoting drugs.

[0013] As the preferred technical solution:

[0014] The composite dressing with a time-sequential response and functional synergy as described above, wherein the thermosensitive micro-nano fiber membrane loaded with an angiogenesis-promoting drug is prepared by sequentially adding polyacrylonitrile, a difatty acid phase change material, and an angiogenesis-promoting drug to N,N-dimethylformamide to prepare a spinning solution, followed by electrospinning;

[0015] The fiber diameter of the thermosensitive micro-nanofiber membrane loaded with pro-angiogenic drugs is 0.5~48μm.

[0016] The present invention also provides a method for preparing a composite dressing with temporal response and functional synergy as described above, wherein a thermosensitive micro-nanofiber membrane loaded with angiogenesis-promoting drugs obtained by electrospinning is placed on a PVA-GOx-MnO2 hydrogel precursor solution or immersed in a PVA-GOx-MnO2 hydrogel precursor solution, and demolded after cross-linking treatment to obtain a composite dressing with temporal response and functional synergy.

[0017] As the preferred technical solution:

[0018] The preparation method of the composite dressing having temporal response and functional synergy as described above comprises the following specific steps:

[0019] (1) Preparation of PVA-GOx-MnO2 hydrogel precursor solution: Dissolve polyvinyl alcohol in deionized water and heat and stir at 70-120°C until completely dissolved to obtain a polyvinyl alcohol solution. After the solution is cooled, glucose oxidase and MnO2 nanoparticles are added in an ice bath (-4-4°C) and stirred to obtain a PVA-GOx-MnO2 hydrogel precursor solution.

[0020] (2) Preparation of difatty acid phase change material: lauric acid and stearic acid were mixed, stirred evenly under heating conditions of 80-120°C, and then cooled, ground, and dried in sequence to obtain difatty acid phase change material;

[0021] (3) Preparing a spinning solution: adding polyacrylonitrile, the difatty acid phase change material obtained in step (2), and the angiogenesis-promoting drug to N,N-dimethylformamide in sequence, stirring evenly, and obtaining a spinning solution;

[0022] (4) Preparing a thermosensitive micro-nanofiber membrane loaded with angiogenic drugs: electrospinning the spinning solution obtained in step (3) to obtain a thermosensitive micro-nanofiber membrane loaded with angiogenic drugs;

[0023] (5) injecting the PVA-GOx-MnO2 hydrogel precursor solution obtained in step (1) into a mold, placing the thermosensitive micro-nanofiber membrane loaded with angiogenic drugs obtained in step (4) on the PVA-GOx-MnO2 hydrogel precursor solution or immersing it in the PVA-GOx-MnO2 hydrogel precursor solution, performing multiple freeze-thaw cycles, and obtaining a composite dressing with temporal response and functional synergy after demolding;

[0024] Among them, there are two ways to immerse the thermosensitive micro-nano fiber membrane in the PVA-GOx-MnO2 hydrogel precursor solution: ① Pressing immersion method: Place the thermosensitive micro-nano fiber membrane on top of the PVA-GOx-MnO2 hydrogel precursor solution, use tweezers to gently press the thermosensitive micro-nano fiber membrane and immerse it in the PVA-GOx-MnO2 hydrogel precursor solution, so that the fiber membrane is completely immersed in the solution, and then perform freeze-thaw molding treatment to make the thermosensitive micro-nano fiber membrane stably embedded in the PVA-GOx-MnO2 hydrogel structure; ② Distributed casting method: First inject part of the PVA-GOx-MnO2 precursor solution into the mold, then place the thermosensitive micro-nano fiber membrane on the surface of the solution, and then cover the remaining PVA-GOx-MnO2 precursor solution on the thermosensitive micro-nano fiber membrane, and then use a cyclic freeze-thaw process to achieve overall molding and bonding.

[0025] In the method for preparing a composite dressing having a temporal response and functional synergy as described above, in step (1), the degree of polymerization of polyvinyl alcohol is 1700±50, the degree of alcoholysis is 88~99.8%, and the concentration of the polyvinyl alcohol solution is 5~25wt%; the amount of glucose oxidase added to the PVA-GOx-MnO2 hydrogel precursor solution is 0.01~2wt%, and the amount of MnO2 nanoparticles added is 0.02~0.06wt%.

[0026] The temperature reached by the photothermal effect of MnO2 is closely related to the content of MnO2 in the hydrogel precursor solution. Experiments have shown that when the content is 0.02wt%, the local temperature can rise to above 38°C under near-infrared light (NIR) irradiation, and when the content is 0.06wt%, the local temperature can rise to above 50°C under NIR irradiation. The content used should match the phase change temperature of the phase change material to ensure controlled drug release. In addition, drug release experiments ( Figure 4 ) also verified the feasibility of the present invention.

[0027] The method for preparing a composite dressing having a time-sequential response and a synergistic function as described above, wherein the particle size of the MnO2 nanoparticles in step (1) is 10-25 nm; the method for synthesizing the MnO2 nanoparticles comprises: dissolving potassium permanganate and ascorbic acid in deionized water to obtain a potassium permanganate solution and an ascorbic acid solution, adding the ascorbic acid solution to the potassium permanganate solution under stirring conditions of 400-3000 r / min, and after the reaction is completed, centrifuging and washing for multiple times, and drying to obtain dry MnO2 nanoparticles;

[0028] The concentration of the potassium permanganate solution is 5-30 mg / mL, the concentration of the ascorbic acid solution is 5-35 mg / mL, and the volume ratio of the potassium permanganate solution to the ascorbic acid solution is 1-3:3-1;

[0029] The reaction time is 0.5~6h.

[0030] In the preparation method of a composite dressing with a time-sequential response and functional synergy as described above, the mass ratio of lauric acid to stearic acid in step (2) is 5-3:1-2, and the phase change temperature of the difatty acid phase change material is 38-50°C. The phase change temperature range of the difatty acid phase change material is set to 38-50°C, based on the following: ① ensuring that the drug is not released when not triggered, maintaining the controlled release function. The local temperature of diabetic chronic wounds is usually 35-37°C. If the phase change temperature is lower than the wound temperature, the phase change material will melt after the dressing is attached to the wound, resulting in drug release, and the design goals of "on-demand release" and "stage response" cannot be achieved. Therefore, the phase change temperature should be slightly higher than the local temperature of the wound; ② ensuring clinical safety and comfort: if the phase change temperature is set too high (>50°C), the local tissue temperature will be too high, there is a risk of thermal damage, and even skin burns or local inflammatory reactions will be caused, affecting wound healing. Therefore, the present invention sets the upper limit of the phase change temperature to 50°C, taking into account both treatment efficiency and patient comfort.

[0031] In the method for preparing a composite dressing having a temporal response and functional synergy as described above, in the spinning solution of step (3), the concentration of polyacrylonitrile is 15-25 wt%, the concentration of the difatty acid phase change material is 5-15 wt%, and the concentration of the angiogenesis-promoting drug is 1-10 wt%.

[0032] Pro-angiogenic drugs do not refer to a specific type of pro-angiogenic drug, but rather refer to all drugs or bioactive substances that have the ability to promote local tissue angiogenesis, including but not limited to: deferoxamine (DFO), curcumin, vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), etc. Those skilled in the art may select other drugs or active ingredients with pro-angiogenic effects to replace or supplement according to actual treatment needs, and all of them should fall within the scope of protection of the present invention.

[0033] In the method for preparing a composite dressing having a temporal response and a synergistic functional effect as described above, the electrospinning process parameters in step (4) are: ambient temperature 20-40°C, relative humidity 20-60%, needle gauge 14-20G, voltage 8-20kV, receiving distance 10-20cm, spinning rate 0.1-2mL / h, and drum speed 100-200rpm.

[0034] The application of a composite dressing with a temporal response and functional synergy as described in any of the above items is used as a material for repairing chronic diabetic wounds. The two-layer structure in the composite dressing achieves orderly connection and functional synergy in the temporal sequence and local spatial area, constructing a multi-stage treatment path with a spatiotemporal cascade effect. The composite dressing can preferentially improve the local microenvironment after contacting the wound, and trigger the release of angiogenic drugs under near-infrared light irradiation, realizing the whole process of treatment from microenvironment regulation to vascular regeneration, significantly improving the healing efficiency and treatment safety of diabetic wounds.

[0035] Principle of the invention:

[0036] This invention not only solves the problems of existing diabetic wound dressings in terms of weak microenvironment regulation, mismatched drug release timing, and low angiogenesis efficiency, but also realizes a full-process intervention system from basic support to advanced repair by integrating the "cascade catalysis-photothermal response-functional synergy" mechanism. Specifically:

[0037] like Figure 1 As shown, the PVA-GOx-MnO2 hydrogel layer in the composite dressing of the present invention spontaneously undergoes a cascade of catalytic reactions upon contact with diabetic chronic wounds: glucose oxidase (GOx) catalyzes the high concentration of glucose in the wound to produce gluconic acid and H2O2. MnO2 nanoparticles then further catalyze the decomposition of H2O2 into oxygen and water, effectively clearing the local high-sugar environment, providing oxygen, and alleviating oxidative stress. This improves the foundation for tissue repair and provides a favorable microenvironment for subsequent angiogenesis. The thermosensitive micro-nanofiber membrane is loaded with an angiogenic drug. Under near-infrared light irradiation, the photothermal effect generated by the MnO2 causes the thermosensitive material to melt, enabling controlled release of the angiogenic drug. This mechanism avoids the passive diffusion of drugs in traditional dressings, ensuring drug release only at the appropriate time, improving drug utilization and reducing the risk of toxicity, thereby demonstrating enhanced therapeutic precision and safety.

[0038] That is, the present invention constructs a multi-stage treatment system driven by the "space-time cascade effect" through functional zoning design: the first stage: the hydrogel layer removes glucose, supplies oxygen and relieves oxidative stress; the second stage: under external near-infrared light irradiation, the photothermal effect generated by MnO2 triggers the thermosensitive micro-nanofiber membrane to release drugs, promoting angiogenesis; this progressive treatment strategy effectively improves the matching degree and functional synergy of treatment at each stage, providing patients with chronic diabetic wounds with a safer and more effective treatment option.

[0039] Without the first-stage microenvironmental regulation, i.e., the lack of improvement of the adverse microenvironment of diabetic chronic wounds, such as local high glucose, hypoxia, and oxidative stress, the second-stage pro-angiogenesis therapy will be adversely affected as follows:

[0040] ① Chronic diabetic wounds have distinct staged healing characteristics. During the inflammatory phase, the local microenvironment is typically characterized by high glucose, hypoxia, enhanced oxidative stress, and elevated levels of inflammatory factors. Directly releasing angiogenic drugs during this phase can hinder their efficacy due to limited cell activity and difficulty activating the corresponding pathways. Inactivation or premature release of the drug may even lead to localized waste or toxicity accumulation, compromising treatment safety.

[0041] ② Improving the microenvironment is a prerequisite for promoting angiogenesis. The first stage, through a cascade of catalytic reactions in the hydrogel layer, reduces blood sugar, provides oxygen, and alleviates oxidative stress, providing a good foundation for tissue repair for subsequent treatment. Only after this stage is completed will the wound enter the proliferation phase suitable for angiogenesis, at which point triggering drug release can achieve a highly effective angiogenic effect.

[0042] Therefore, the present invention proposes a progressive treatment strategy of "first improving the microenvironment and then triggering drug release", which ensures that the drug is released only at the appropriate time, thereby significantly improving the drug efficacy and treatment safety. This is one of the key innovations that distinguishes the present invention from the existing technology.

[0043] Compared with existing technologies, the present invention systematically constructs an orderly treatment pathway of "improving the microenvironment first and then triggering angiogenesis", achieving significant technical effects:

[0044] Actively regulate the microenvironment: Utilize the PVA-GOx-MnO2 hydrogel layer to actively eliminate local high sugar, supply oxygen and relieve oxidative stress through cascade catalytic reactions, creating an ideal tissue repair foundation for subsequent treatment.

[0045] Externally controlled precise drug release: Angiogenic drugs are encapsulated in a thermosensitive micro-nanofiber membrane containing difatty acid phase change material. Under NIR irradiation, the photothermal effect generated by MnO2 triggers drug release, achieving on-demand and controllable drug release.

[0046] Functional synergy and temporal response: The two-layer structure advances step by step, realizing the whole process intervention from basic support to advanced repair, effectively solving the problems of improper drug release timing and unstable efficacy in existing technologies.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] (1) The composite dressing of the present invention with temporal response and functional synergy not only solves the problems of existing diabetic wound dressings in terms of weak microenvironment regulation ability, mismatched drug release timing, and low angiogenesis efficiency, but also realizes a full-process intervention system from basic support to advanced repair by integrating the "cascade catalysis-photothermal response-functional synergy" mechanism.

[0049] (2) The present invention provides a composite dressing with a time-dependent response and functional synergy. The PVA-GOx-MnO2 hydrogel layer can spontaneously undergo a cascade catalytic reaction after contact with diabetic chronic wounds: glucose oxidase (GOx) catalyzes the high concentration of glucose in the local wound to produce gluconic acid and H2O2, and then MnO2 nanoparticles further catalyze the decomposition of H2O2 into oxygen and water, thereby clearing the local high-sugar environment of the wound, supplying oxygen, and alleviating oxidative stress, thereby improving the basic conditions for tissue repair and providing a good microenvironmental support for subsequent angiogenesis.

[0050] (3) The present invention provides a method for preparing a composite dressing with temporal response and functional synergy, which constructs a multi-stage treatment system driven by a "time-space cascade effect" through functional zoning design. This progressive treatment strategy effectively improves the matching degree and functional synergy of treatment at each stage, providing patients with chronic diabetic wounds with a safer and more effective treatment option.

[0051] (4) The present invention provides a composite dressing with a time-dependent response and functional synergy. The composite dressing can preferentially improve the local microenvironment after contacting the wound and trigger the release of angiogenic drugs under near-infrared light irradiation, thereby achieving a full-process treatment from microenvironment regulation to angiogenesis, significantly improving the healing efficiency and treatment safety of diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 Schematic diagram of the mechanism of action of the composite dressing with temporal response and functional synergy of the present invention;

[0053] Figure 2 This is an electron microscope image of the microstructure of the composite dressing prepared in Example 3 of the present invention;

[0054] Figure 3 This is an in vitro drug release curve of the composite dressing prepared in Example 3 of the present invention;

[0055] Figure 4 Graph showing the cytotoxicity test results of the composite dressings prepared in Examples 1 to 7 of the present invention;

[0056] Figure 5 This is a diagram of in vitro angiogenesis of the composite dressing prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0057] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used in limiting the scope of the present invention.In addition, should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.

[0058] The test methods involved in the performance indicators of the present invention are as follows:

[0059] In vitro drug release behavior test: The composite dressing samples were immersed in PBS solution (0.01M, pH=7.4) and NIR (wavelength 808nm, light intensity 1W / cm 2 ) for 30 minutes. At set time points, 2 mL of solution was removed and the absorbance at the characteristic peak was measured using a UV-visible spectrophotometer. The drug concentration in the solution at each sampling time point was determined using the standard equation. The cumulative drug release rate was calculated and the drug release curve was plotted using the following formula: . C i is the drug concentration obtained in the i-th test, m is the mass of the composite dressing (μg), a is the mass of the drug (μg), and b is the mass of other components in the composite dressing except the drug (μg).

[0060] Cytotoxicity Testing: Before testing, composite dressing samples were sterilized by placing them in an alcohol fumigation jar for 24 hours. Human umbilical vein endothelial cells (HUVECs) were seeded in 24-well plates at a density of 80,000 cells / well, with three replicates per well. After incubation for 4 hours until cells adhered, cells incubated without sample served as the control group; cells incubated with sample for 24 hours served as the experimental group. After incubation, the cells were washed three times with PBS, and CCK-8 reagent was added. The cells were incubated at 37°C in the dark for 2 hours. Absorbance at 450 nm was measured using a microplate reader, and cell viability was calculated.

[0061] In vitro angiogenesis test: Using the composite dressing as a sample, Matrigel (manufacturer: Solarbio, catalog number: M8370) was placed at 4°C for 12 hours to melt, and the pipette tip and 24-well plate were placed in the refrigerator for pre-cooling. A cell slide was placed in the well plate, and 130 μL of Matrigel was drawn up with a pre-cooled pipette tip and added to the well plate and spread flat. The well plate was placed in an incubator for 30 minutes to allow the Matrigel to completely solidify. The well plate was removed, cells were inoculated at a cell density of 40,000 cells / well, and samples were placed. NIR (wavelength 808 nm, light intensity 1 W / cm 2 After 30 minutes of irradiation, the plate was placed in an incubator and incubated for 8 hours. Cells cultured without sample were used as the control group, and cells cultured with sample were used as the experimental group.

[0062] Example 1

[0063] A method for preparing a composite dressing with temporal response and functional synergy, comprising the following steps:

[0064] (1) Preparation of PVA-GOx-MnO2 hydrogel precursor solution:

[0065] (1.1) Synthesis of MnO2 nanoparticles:

[0066] Potassium permanganate and ascorbic acid were dissolved in deionized water to obtain a potassium permanganate solution with a concentration of 21 mg / mL and an ascorbic acid solution with a concentration of 23.5 mg / mL, and the ascorbic acid solution was added to the potassium permanganate solution under stirring at a speed of 1000 r / min and reacted for 1 hour. After the reaction, the mixture was centrifuged, washed with anhydrous ethanol 4 times, and washed with deionized water 2 times, and dried at 90°C for 12 hours to obtain MnO2 nanoparticles with an average particle size of 17±0.4 nm.

[0067] Wherein, the volume ratio of potassium permanganate solution to ascorbic acid solution is 1:1;

[0068] (1.2) Dissolve polyvinyl alcohol (PVA) 1797 in deionized water under heating and stirring at 90°C until completely dissolved to obtain a 8 wt% PVA solution.

[0069] (1.3) After the polyvinyl alcohol solution has cooled, glucose oxidase (manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., catalog number: S10021) and MnO2 nanoparticles are added to the solution in an ice bath at -2°C and stirred to obtain a PVA-GOx-MnO2 hydrogel precursor solution.

[0070] Among them, the addition amount of glucose oxidase in the PVA-GOx-MnO2 hydrogel precursor solution is 0.05wt%, and the addition amount of MnO2 nanoparticles is 0.04wt%;

[0071] (2) Preparation of difatty acid phase change material: lauric acid and stearic acid were mixed, stirred evenly under heating conditions of 90°C, cooled at room temperature, ground, and dried at 25°C to obtain difatty acid phase change material;

[0072] The mass ratio of lauric acid to stearic acid is 4:1, and the phase change temperature of the difatty acid phase change material is 40°C.

[0073] (3) Preparing a spinning solution: polyacrylonitrile (manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., product number: P823208), the difatty acid phase change material obtained in step (2), and deferoxamine were sequentially added to N,N-dimethylformamide and stirred to obtain a spinning solution;

[0074] In the spinning solution, the concentration of polyacrylonitrile is 21wt%, the concentration of difatty acid phase change material is 9wt%, and the concentration of deferoxamine is 5wt%;

[0075] (4) Preparation of thermosensitive micro-nano fiber membrane: The spinning solution obtained in step (3) was used for electrospinning. After the spinning was completed, the fiber membrane was placed in a vacuum oven at 30°C and dried for 10 hours to obtain a thermosensitive micro-nano fiber membrane; the average fiber diameter in the thermosensitive micro-nano fiber membrane was 2.1±0.3 μm;

[0076] The electrospinning process parameters were as follows: ambient temperature 25°C, relative humidity 50%, needle gauge 18G, voltage 10 kV, receiving distance 18 cm, spinning rate 1 mL / h, and drum speed 140 rpm;

[0077] (5) 0.3 mL of the PVA-GOx-MnO2 hydrogel precursor solution obtained in step (1) was injected into a circular mold with a diameter of 1 cm, and the thermosensitive micro-nanofiber membrane obtained in step (4) was cut into discs with a diameter of 1 cm, immersed in the PVA-GOx-MnO2 hydrogel precursor solution, and subjected to three freeze-thaw cycles. After demolding, a composite dressing with temporal response and functional synergy was obtained;

[0078] Among them, during the freeze-thaw cycle treatment, the freezing temperature is -20℃, the freezing time is 20h, the thawing temperature is 25℃, and the thawing time is 4h.

[0079] The final composite dressing with temporal response and functional synergy is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a thermosensitive micro-nanofiber membrane layer; the thermosensitive micro-nanofiber membrane is a thermosensitive micro-nanofiber membrane loaded with the angiogenesis-promoting drug deferoxamine; the composite dressing with temporal response and functional synergy is used as a repair material for chronic diabetic wounds; the cumulative drug release of the composite dressing with temporal response and functional synergy within 48 hours is 47.75%, which can achieve controlled release of angiogenesis-promoting drugs; such as Figure 4 As shown, the cell viability of the experimental group was 108.9%, indicating that the sample had no cytotoxicity to HUVECs.

[0080] Example 2

[0081] A method for preparing a composite dressing with temporal response and functional synergy, comprising the following steps:

[0082] (1) Preparation of PVA-GOx-MnO2 hydrogel precursor solution:

[0083] (1.1) Synthesis of MnO2 nanoparticles:

[0084] Potassium permanganate and ascorbic acid were dissolved in deionized water to obtain a potassium permanganate solution with a concentration of 13 mg / mL and an ascorbic acid solution with a concentration of 5 mg / mL. The ascorbic acid solution was added to the potassium permanganate solution under stirring at a speed of 1000 r / min and reacted for 1 hour. After the reaction, the mixture was centrifuged, washed with anhydrous ethanol 4 times, washed with deionized water 2 times, and dried at 90°C for 12 hours to obtain MnO2 nanoparticles with an average particle size of 12±0.6 nm.

[0085] Wherein, the volume ratio of potassium permanganate solution to ascorbic acid solution is 1:3;

[0086] (1.2) Dissolve polyvinyl alcohol (PVA) 1797 in deionized water under heating and stirring at 90°C until completely dissolved to obtain a 8 wt% PVA solution.

[0087] (1.3) After the polyvinyl alcohol solution has cooled, glucose oxidase (manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., catalog number: S10021) and MnO2 nanoparticles are added to the solution in an ice bath at -2°C and stirred to obtain a PVA-GOx-MnO2 hydrogel precursor solution.

[0088] Among them, the addition amount of glucose oxidase in the PVA-GOx-MnO2 hydrogel precursor solution is 0.05wt%, and the addition amount of MnO2 nanoparticles is 0.04wt%;

[0089] (2) Preparation of difatty acid phase change material: lauric acid and stearic acid were mixed, stirred evenly under heating conditions of 90°C, cooled at room temperature, ground, and dried at 25°C to obtain difatty acid phase change material;

[0090] The mass ratio of lauric acid to stearic acid is 4:1, and the phase change temperature of the difatty acid phase change material is 40°C.

[0091] (3) Preparing a spinning solution: polyacrylonitrile (manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., product number: P823208), the difatty acid phase change material obtained in step (2), and deferoxamine were sequentially added to N,N-dimethylformamide and stirred to obtain a spinning solution;

[0092] In the spinning solution, the concentration of polyacrylonitrile is 21wt%, the concentration of difatty acid phase change material is 9wt%, and the concentration of deferoxamine is 5wt%;

[0093] (4) Preparation of thermosensitive micro-nano fiber membrane: The spinning solution obtained in step (3) was used for electrospinning. After the spinning was completed, the fiber membrane was placed in a vacuum oven at 30°C and dried for 10 hours to obtain a thermosensitive micro-nano fiber membrane; the average fiber diameter in the thermosensitive micro-nano fiber membrane was 2.1±0.3 μm;

[0094] The electrospinning process parameters were as follows: ambient temperature 25°C, relative humidity 50%, needle gauge 18G, voltage 10 kV, receiving distance 18 cm, spinning rate 1 mL / h, and drum speed 140 rpm;

[0095] (5) 0.3 mL of the PVA-GOx-MnO2 hydrogel precursor solution obtained in step (1) was injected into a circular mold with a diameter of 1 cm, and the thermosensitive micro-nanofiber membrane obtained in step (4) was cut into 1 cm diameter discs, immersed in the PVA-GOx-MnO2 hydrogel precursor solution, and subjected to three freeze-thaw cycles. After demolding, a composite dressing with temporal response and functional synergy was obtained;

[0096] Among them, during the freeze-thaw cycle treatment, the freezing temperature is -20℃, the freezing time is 20h, the thawing temperature is 25℃, and the thawing time is 4h.

[0097] The final composite dressing with temporal response and functional synergy is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a thermosensitive micro-nano fiber membrane layer; the thermosensitive micro-nano fiber membrane is a thermosensitive micro-nano fiber membrane loaded with the angiogenesis-promoting drug deferoxamine; the composite dressing with temporal response and functional synergy is used as a repair material for chronic diabetic wounds; the cumulative drug release of the composite dressing with temporal response and functional synergy within 48 hours is 46.54%, which can achieve controlled release of angiogenesis-promoting drugs. Figure 4 As shown, the cell viability of the experimental group was 112.5%, indicating that the sample had no cytotoxicity to HUVECs.

[0098] Example 3

[0099] A method for preparing a composite dressing with temporal response and functional synergy, comprising the following steps:

[0100] (1) Preparation of PVA-GOx-MnO2 hydrogel precursor solution:

[0101] (1.1) Synthesis of MnO2 nanoparticles:

[0102] Potassium permanganate and ascorbic acid were dissolved in deionized water to obtain a potassium permanganate solution with a concentration of 21 mg / mL and an ascorbic acid solution with a concentration of 23.5 mg / mL, and the ascorbic acid solution was added to the potassium permanganate solution under stirring at a speed of 1000 r / min and reacted for 1 hour. After the reaction, the mixture was centrifuged, washed with anhydrous ethanol 4 times, and washed with deionized water 2 times, and dried at 90°C for 12 hours to obtain MnO2 nanoparticles with an average particle size of 17±0.4 nm.

[0103] Wherein, the volume ratio of potassium permanganate solution to ascorbic acid solution is 1:1;

[0104] (1.2) Dissolve polyvinyl alcohol (PVA) 1797 in deionized water under heating and stirring at 90°C until completely dissolved to obtain a 8 wt% PVA solution.

[0105] (1.3) After the polyvinyl alcohol solution has cooled, glucose oxidase (manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., catalog number: S10021) and MnO2 nanoparticles are added to the solution in an ice bath at -2°C and stirred to obtain a PVA-GOx-MnO2 hydrogel precursor solution.

[0106] Among them, the addition amount of glucose oxidase in the PVA-GOx-MnO2 hydrogel precursor solution is 0.05wt%, and the addition amount of MnO2 nanoparticles is 0.04wt%;

[0107] (2) Preparation of difatty acid phase change material: lauric acid and stearic acid were mixed, stirred evenly under heating conditions of 90°C, cooled at room temperature, ground, and dried at 25°C to obtain difatty acid phase change material;

[0108] The mass ratio of lauric acid to stearic acid is 4:1, and the phase change temperature of the difatty acid phase change material is 40°C.

[0109] (3) Preparing a spinning solution: polyacrylonitrile (manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., product number: P823208), the difatty acid phase change material obtained in step (2), and deferoxamine were sequentially added to N,N-dimethylformamide and stirred to obtain a spinning solution;

[0110] In the spinning solution, the concentration of polyacrylonitrile is 18wt%, the concentration of difatty acid phase change material is 12wt%, and the concentration of deferoxamine is 5wt%;

[0111] (4) Preparation of thermosensitive micro-nano fiber membrane: The spinning solution obtained in step (3) was used for electrospinning. After the spinning was completed, the fiber membrane was placed in a vacuum oven at 30°C and dried for 10 hours to obtain a thermosensitive micro-nano fiber membrane; the average fiber diameter in the thermosensitive micro-nano fiber membrane was 1.4±0.2 μm;

[0112] The electrospinning process parameters were as follows: ambient temperature 25°C, relative humidity 50%, needle gauge 18G, voltage 10 kV, receiving distance 18 cm, spinning rate 1 mL / h, and drum speed 140 rpm;

[0113] (5) 0.3 mL of the PVA-GOx-MnO2 hydrogel precursor solution obtained in step (1) was injected into a circular mold with a diameter of 1 cm, and the thermosensitive micro-nanofiber membrane obtained in step (4) was cut into discs with a diameter of 1 cm, immersed in the PVA-GOx-MnO2 hydrogel precursor solution, and subjected to three freeze-thaw cycles. After demolding, a composite dressing with temporal response and functional synergy was obtained;

[0114] Among them, during the freeze-thaw cycle treatment, the freezing temperature is -20℃, the freezing time is 20h, the thawing temperature is 25℃, and the thawing time is 4h.

[0115] The final composite dressing with temporal response and functional synergy is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a thermosensitive micro-nanofiber membrane layer; the thermosensitive micro-nanofiber membrane is a thermosensitive micro-nanofiber membrane loaded with the pro-angiogenic drug deferoxamine; the composite dressing with temporal response and functional synergy is used as a chronic diabetic wound repair material.

[0116] like Figure 2 As shown, the final composite dressing with temporal response and functional synergy is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a thermosensitive micro-nanofiber membrane layer; the thermosensitive micro-nanofiber membrane is a thermosensitive micro-nanofiber membrane loaded with pro-angiogenic drugs; the composite dressing with temporal response and functional synergy is used as a chronic diabetic wound repair material.

[0117] like Figure 3 As shown, the composite dressing with a temporal response and synergistic function can achieve controlled release of angiogenic drugs, with the cumulative drug release reaching 81.31% within 48 hours. This indicates that under NIR irradiation, MnO2 nanoparticles can absorb light energy and convert it into heat energy, triggering a phase transition in the phase change material in the fiber membrane, thereby releasing the drug. This result verifies the reliability of the sample's drug release mechanism and avoids the "burst release" or "premature release" problems common in traditional dressings.

[0118] like Figure 4 As shown, the cell viability of the experimental group was 118.4%, indicating that the sample had no cytotoxicity to HUVECs.

[0119] like Figure 5 As shown, after 8 hours of cell incubation, no tubular structures formed in the control group, while tubular structures were clearly observed in the experimental group. This is because the angiogenic drugs in the sample were released under NIR irradiation, effectively promoting angiogenesis. This result shows that during the healing process of diabetic wounds, the composite dressing prepared in Example 3 can achieve efficient vascularization of damaged tissue more quickly, providing a strong guarantee for tissue repair and regeneration.

[0120] Example 4

[0121] A method for preparing a composite dressing with temporal response and functional synergy, comprising the following steps:

[0122] (1) Preparation of PVA-GOx-MnO2 hydrogel precursor solution:

[0123] (1.1) Synthesis of MnO2 nanoparticles:

[0124] Potassium permanganate and ascorbic acid were dissolved in deionized water to obtain a potassium permanganate solution with a concentration of 21 mg / mL and an ascorbic acid solution with a concentration of 23.5 mg / mL, and the ascorbic acid solution was added to the potassium permanganate solution under stirring at a speed of 1000 r / min and reacted for 1 hour. After the reaction, the mixture was centrifuged, washed with anhydrous ethanol 4 times, and washed with deionized water 2 times, and dried at 90°C for 12 hours to obtain MnO2 nanoparticles with an average particle size of 17±0.4 nm.

[0125] Wherein, the volume ratio of potassium permanganate solution to ascorbic acid solution is 1:1;

[0126] (1.2) Dissolve polyvinyl alcohol (PVA) 1797 in deionized water under heating and stirring at 90°C until completely dissolved to obtain a 8 wt% PVA solution.

[0127] (1.3) After the polyvinyl alcohol solution has cooled, glucose oxidase (manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., catalog number: S10021) and MnO2 nanoparticles are added to the solution in an ice bath at -2°C and stirred to obtain a PVA-GOx-MnO2 hydrogel precursor solution.

[0128] Among them, the addition amount of glucose oxidase in the PVA-GOx-MnO2 hydrogel precursor solution is 0.05wt%, and the addition amount of MnO2 nanoparticles is 0.04wt%;

[0129] (2) Preparation of difatty acid phase change material: lauric acid and stearic acid were mixed, stirred evenly under heating conditions of 90°C, cooled at room temperature, ground, and dried at 25°C to obtain difatty acid phase change material;

[0130] Among them, the mass ratio of lauric acid to stearic acid is 5:1.5, and the phase change temperature of the difatty acid phase change material is 43°C;

[0131] (3) Preparing a spinning solution: polyacrylonitrile (manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., product number: P823208), the difatty acid phase change material obtained in step (2), and deferoxamine were sequentially added to N,N-dimethylformamide and stirred to obtain a spinning solution;

[0132] In the spinning solution, the concentration of polyacrylonitrile is 21wt%, the concentration of difatty acid phase change material is 9wt%, and the concentration of deferoxamine is 5wt%;

[0133] (4) Preparation of thermosensitive micro-nano fiber membrane: The spinning solution obtained in step (3) was used for electrospinning. After the spinning was completed, the fiber membrane was placed in a vacuum oven at 30°C and dried for 10 hours to obtain a thermosensitive micro-nano fiber membrane; the average fiber diameter in the thermosensitive micro-nano fiber membrane was 2±0.4 μm;

[0134] The electrospinning process parameters were as follows: ambient temperature 25°C, relative humidity 50%, needle gauge 18G, voltage 10 kV, receiving distance 18 cm, spinning rate 1 mL / h, and drum speed 140 rpm;

[0135] (5) 0.3 mL of the PVA-GOx-MnO2 hydrogel precursor solution obtained in step (1) was injected into a circular mold with a diameter of 1 cm, and the thermosensitive micro-nanofiber membrane obtained in step (4) was cut into discs with a diameter of 1 cm, immersed in the PVA-GOx-MnO2 hydrogel precursor solution, and subjected to three freeze-thaw cycles. After demolding, a composite dressing with temporal response and functional synergy was obtained;

[0136] Among them, during the freeze-thaw cycle treatment, the freezing temperature is -20℃, the freezing time is 20h, the thawing temperature is 25℃, and the thawing time is 4h.

[0137] The final composite dressing with temporal response and functional synergy is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a thermosensitive micro-nanofiber membrane layer; the thermosensitive micro-nanofiber membrane is a thermosensitive micro-nanofiber membrane loaded with the pro-angiogenic drug deferoxamine; the composite dressing with temporal response and functional synergy is used as a chronic diabetic wound repair material.

[0138] The cumulative drug release of the composite dressing with temporal response and functional synergy within 48 hours was 45.73%, which can achieve controlled release of angiogenesis-promoting drugs. Figure 4 As shown, the cell viability of the experimental group was 109.2%, indicating that the sample had no cytotoxicity to HUVECs.

[0139] Example 5

[0140] A method for preparing a composite dressing with temporal response and functional synergy, comprising the following steps:

[0141] (1) Preparation of PVA-GOx-MnO2 hydrogel precursor solution:

[0142] (1.1) Synthesis of MnO2 nanoparticles:

[0143] Potassium permanganate and ascorbic acid were dissolved in deionized water to obtain a potassium permanganate solution with a concentration of 21 mg / mL and an ascorbic acid solution with a concentration of 23.5 mg / mL, and the ascorbic acid solution was added to the potassium permanganate solution under stirring at a speed of 1000 r / min and reacted for 1 hour. After the reaction, the mixture was centrifuged, washed with anhydrous ethanol 4 times, and washed with deionized water 2 times, and dried at 90°C for 12 hours to obtain MnO2 nanoparticles with an average particle size of 17±0.4 nm.

[0144] Wherein, the volume ratio of potassium permanganate solution to ascorbic acid solution is 1:1;

[0145] (1.2) Dissolve polyvinyl alcohol (PVA) 1797 in deionized water under heating and stirring at 90°C until completely dissolved to obtain a 8 wt% PVA solution.

[0146] (1.3) After the polyvinyl alcohol solution has cooled, glucose oxidase (manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., catalog number: S10021) and MnO2 nanoparticles are added to the solution in an ice bath at -2°C and stirred to obtain a PVA-GOx-MnO2 hydrogel precursor solution.

[0147] Among them, the addition amount of glucose oxidase in the PVA-GOx-MnO2 hydrogel precursor solution is 0.05wt%, and the addition amount of MnO2 nanoparticles is 0.04wt%;

[0148] (2) Preparation of difatty acid phase change material: lauric acid and stearic acid were mixed, stirred evenly under heating conditions of 90°C, cooled at room temperature, ground, and dried at 25°C to obtain difatty acid phase change material;

[0149] The mass ratio of lauric acid to stearic acid is 4:1, and the phase change temperature of the difatty acid phase change material is 40°C.

[0150] (3) Preparation of spinning solution: polyacrylonitrile (manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., product number: P823208), the difatty acid phase change material obtained in step (2), and curcumin (manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., product number: S35425) were added to N,N-dimethylformamide in sequence, and stirred evenly to obtain a spinning solution;

[0151] In the spinning solution, the concentration of polyacrylonitrile is 18wt%, the concentration of difatty acid phase change material is 12wt%, and the concentration of curcumin is 5wt%;

[0152] (4) Preparation of thermosensitive micro-nano fiber membrane: The spinning solution obtained in step (3) was used for electrospinning. After the spinning was completed, the fiber membrane was placed in a vacuum oven at 30°C and dried for 10 hours to obtain a thermosensitive micro-nano fiber membrane; the average fiber diameter in the thermosensitive micro-nano fiber membrane was 1.6±0.4 μm;

[0153] The electrospinning process parameters were as follows: ambient temperature 25°C, relative humidity 50%, needle gauge 18G, voltage 10 kV, receiving distance 18 cm, spinning rate 1 mL / h, and drum speed 140 rpm;

[0154] (5) 0.3 mL of the PVA-GOx-MnO2 hydrogel precursor solution obtained in step (1) was injected into a circular mold with a diameter of 1 cm, and the thermosensitive micro-nanofiber membrane obtained in step (4) was cut into discs with a diameter of 1 cm, placed in the PVA-GOx-MnO2 hydrogel precursor solution, and subjected to three freeze-thaw cycles. After demolding, a composite dressing with temporal response and functional synergy was obtained;

[0155] Among them, during the freeze-thaw cycle treatment, the freezing temperature is -20℃, the freezing time is 20h, the thawing temperature is 25℃, and the thawing time is 4h.

[0156] The final composite dressing with temporal response and functional synergy is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a thermosensitive micro-nanofiber membrane layer; the thermosensitive micro-nanofiber membrane is a thermosensitive micro-nanofiber membrane loaded with the pro-angiogenic drug curcumin; the composite dressing with temporal response and functional synergy is used as a chronic diabetic wound repair material.

[0157] The cumulative drug release of the composite dressing with temporal response and functional synergy within 48 hours was 79.64%, which can achieve controlled release of angiogenesis-promoting drugs. Figure 4 As shown, the cell viability of the experimental group was 121.6%, indicating that the sample had no cytotoxicity to HUVECs.

[0158] Example 6

[0159] A method for preparing a composite dressing with temporal response and functional synergy, comprising the following steps:

[0160] (1) Preparation of PVA-GOx-MnO2 hydrogel precursor solution:

[0161] (1.1) Synthesis of MnO2 nanoparticles:

[0162] Potassium permanganate and ascorbic acid were dissolved in deionized water to obtain a potassium permanganate solution with a concentration of 5 mg / mL and an ascorbic acid solution with a concentration of 18 mg / mL. The ascorbic acid solution was added to the potassium permanganate solution under stirring at a speed of 400 r / min and reacted for 6 h. After the reaction, the mixture was centrifuged, washed with anhydrous ethanol 4 times, washed with deionized water 2 times, and dried at 90°C for 12 h to obtain MnO2 nanoparticles with an average particle size of 10.5±0.5 nm.

[0163] The volume ratio of potassium permanganate solution to ascorbic acid solution is 3:1;

[0164] (1.2) Dissolve polyvinyl alcohol (PVA) 1788 in deionized water under heating and stirring at 70°C until completely dissolved to obtain a 5 wt% PVA solution.

[0165] (1.3) After the polyvinyl alcohol solution has cooled, glucose oxidase (manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., catalog number: S10021) and MnO2 nanoparticles are added to the solution in an ice bath at -2°C and stirred to obtain a PVA-GOx-MnO2 hydrogel precursor solution.

[0166] Among them, the addition amount of glucose oxidase in the PVA-GOx-MnO2 hydrogel precursor solution is 0.01wt%, and the addition amount of MnO2 nanoparticles is 0.02wt%;

[0167] (2) Preparation of difatty acid phase change material: lauric acid and stearic acid were mixed, stirred evenly under heating conditions of 80°C, cooled at room temperature, ground, and dried at 25°C to obtain difatty acid phase change material;

[0168] Among them, the mass ratio of lauric acid to stearic acid is 5:1, and the phase change temperature of the difatty acid phase change material is 38°C;

[0169] (3) Preparing a spinning solution: polyacrylonitrile (manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., product number: P823208), the difatty acid phase change material obtained in step (2), and deferoxamine were sequentially added to N,N-dimethylformamide and stirred to obtain a spinning solution;

[0170] In the spinning solution, the concentration of polyacrylonitrile is 15wt%, the concentration of difatty acid phase change material is 15wt%, and the concentration of deferoxamine is 1wt%;

[0171] (4) Preparation of thermosensitive micro-nano fiber membrane: The spinning solution obtained in step (3) was used for electrospinning. After the spinning was completed, the fiber membrane was placed in a vacuum oven at 30°C and dried for 10 hours to obtain a thermosensitive micro-nano fiber membrane; the fiber diameter of the thermosensitive micro-nano fiber membrane was 0.7±0.2 μm;

[0172] The electrospinning process parameters were as follows: ambient temperature 20 °C, relative humidity 60%, needle gauge 20G, voltage 20 kV, receiving distance 20 cm, spinning rate 0.1 mL / h, and drum speed 100 rpm.

[0173] (5) 0.3 mL of the PVA-GOx-MnO2 hydrogel precursor solution obtained in step (1) was injected into a circular mold with a diameter of 1 cm, and the thermosensitive micro-nanofiber membrane obtained in step (4) was cut into 1 cm discs and placed on the PVA-GOx-MnO2 hydrogel precursor solution. The mixture was subjected to three freeze-thaw cycles, and a composite dressing with a temporal response and functional synergy was obtained after demolding.

[0174] Among them, during the freeze-thaw cycle treatment, the freezing temperature is -20℃, the freezing time is 20h, the thawing temperature is 25℃, and the thawing time is 4h.

[0175] The final composite dressing with temporal response and functional synergy is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a thermosensitive micro-nanofiber membrane layer; the thermosensitive micro-nanofiber membrane is a thermosensitive micro-nanofiber membrane loaded with the pro-angiogenic drug deferoxamine; the composite dressing with temporal response and functional synergy is used as a chronic diabetic wound repair material.

[0176] The cumulative drug release of the composite dressing with temporal response and functional synergy within 48 hours was 89.56%, which can achieve controlled release of angiogenesis-promoting drugs. Figure 4 As shown, the cell viability of the experimental group was 110.5%, indicating that the sample had no cytotoxicity to HUVECs.

[0177] Example 7

[0178] A method for preparing a composite dressing with temporal response and functional synergy, comprising the following steps:

[0179] (1) Preparation of PVA-GOx-MnO2 hydrogel precursor solution:

[0180] (1.1) Synthesis of MnO2 nanoparticles:

[0181] Potassium permanganate and ascorbic acid were dissolved in deionized water to obtain a potassium permanganate solution with a concentration of 30 mg / mL and an ascorbic acid solution with a concentration of 35 mg / mL, and the ascorbic acid solution was added to the potassium permanganate solution under stirring at a speed of 3000 r / min and reacted for 0.5 h. After the reaction, the mixture was centrifuged, washed with anhydrous ethanol 4 times, and washed with deionized water 2 times, and dried at 90°C for 12 h to obtain MnO2 nanoparticles with an average particle size of 24.2±0.6 nm.

[0182] Wherein, the volume ratio of potassium permanganate solution to ascorbic acid solution is 1:1;

[0183] (1.2) Dissolve polyvinyl alcohol (PVA) 1799 in deionized water under heating and stirring at 120°C until completely dissolved to obtain a 25 wt% PVA solution.

[0184] (1.3) After the polyvinyl alcohol solution has cooled, glucose oxidase (manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., catalog number: S10021) and MnO2 nanoparticles are added to the solution in an ice bath at -2°C and stirred to obtain a PVA-GOx-MnO2 hydrogel precursor solution.

[0185] Among them, the addition amount of glucose oxidase in the PVA-GOx-MnO2 hydrogel precursor solution is 2wt%, and the addition amount of MnO2 nanoparticles is 0.06wt%;

[0186] (2) Preparation of difatty acid phase change material: lauric acid and stearic acid were mixed, stirred evenly under heating conditions of 120°C, cooled at room temperature, ground, and dried at 25°C to obtain difatty acid phase change material;

[0187] The mass ratio of lauric acid to stearic acid is 3:2, and the phase change temperature of the difatty acid phase change material is 50°C.

[0188] (3) Preparing a spinning solution: polyacrylonitrile (manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., product number: P823208), the difatty acid phase change material obtained in step (2), and deferoxamine were sequentially added to N,N-dimethylformamide and stirred to obtain a spinning solution;

[0189] In the spinning solution, the concentration of polyacrylonitrile is 25wt%, the concentration of difatty acid phase change material is 5wt%, and the concentration of deferoxamine is 10wt%;

[0190] (4) Preparation of thermosensitive micro-nano fiber membrane: The spinning solution obtained in step (3) was used for electrospinning. After the spinning was completed, the fiber membrane was placed in a vacuum oven at 30°C and dried for 10 hours to obtain a thermosensitive micro-nano fiber membrane; the average fiber diameter of the thermosensitive micro-nano fiber membrane was 48±0.5 μm;

[0191] The electrospinning process parameters were as follows: ambient temperature 40°C, relative humidity 20%, needle gauge 14G, voltage 8 kV, receiving distance 10 cm, spinning rate 2 mL / h, and drum speed 200 rpm;

[0192] (5) 0.3 mL of the PVA-GOx-MnO2 hydrogel precursor solution obtained in step (1) was injected into a circular mold with a diameter of 1 cm, and the thermosensitive micro-nanofiber membrane obtained in step (4) was cut into 1 cm discs and placed on the PVA-GOx-MnO2 hydrogel precursor solution. The mixture was subjected to three freeze-thaw cycles, and a composite dressing with a temporal response and functional synergy was obtained after demolding.

[0193] Among them, during the freeze-thaw cycle treatment, the freezing temperature is -20℃, the freezing time is 20h, the thawing temperature is 25℃, and the thawing time is 4h.

[0194] The final composite dressing with temporal response and functional synergy is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a thermosensitive micro-nanofiber membrane layer; the thermosensitive micro-nanofiber membrane is a thermosensitive micro-nanofiber membrane loaded with the pro-angiogenic drug deferoxamine; the composite dressing with temporal response and functional synergy is used as a chronic diabetic wound repair material.

[0195] The composite dressing with temporal response and functional synergy has a cumulative drug release of 41.26% within 48 hours, which can achieve controlled release of angiogenesis-promoting drugs. Figure 4 As shown, the cell viability of the composite dressing prepared in this example was 98.74%, indicating that the sample had no cytotoxicity to HUVECs.

Claims

1. A composite dressing with temporal response and functional synergy, characterized by: It is a double-layer composite structure, including a PVA-GOx-MnO2 hydrogel layer and a temperature-sensitive micro-nanofiber membrane layer; The PVA-GOx-MnO2 hydrogel is prepared by cross-linking a PVA-GOx-MnO2 hydrogel precursor solution, which is prepared by adding glucose oxidase and MnO2 nanoparticles to a polyvinyl alcohol solution under ice bath conditions. The thermosensitive micro-nanofiber membrane is a thermosensitive micro-nanofiber membrane loaded with angiogenesis-promoting drugs.

2. The composite dressing with temporal response and functional synergy according to claim 1, characterized in that: The thermosensitive micro-nano fiber membrane loaded with angiogenesis-promoting drugs is prepared by sequentially adding polyacrylonitrile, difatty acid phase change material and angiogenesis-promoting drugs into N,N-dimethylformamide to form a spinning solution, and then electrospinning the solution. The fiber diameter of the thermosensitive micro-nanofiber membrane loaded with pro-angiogenic drugs is 0.5~48μm.

3. The method for preparing a composite dressing with temporal response and functional synergy according to claim 1 or 2, characterized in that: The thermosensitive micro-nanofiber membrane loaded with angiogenic drugs obtained by electrospinning is placed on a PVA-GOx-MnO2 hydrogel precursor solution or immersed in a PVA-GOx-MnO2 hydrogel precursor solution. After cross-linking treatment, it is demolded to obtain a composite dressing with temporal response and functional synergy.

4. The method for preparing a composite dressing with temporal response and functional synergy according to claim 3, characterized in that: The specific steps are as follows: (1) Preparation of PVA-GOx-MnO2 hydrogel precursor solution: Dissolve polyvinyl alcohol in deionized water and heat and stir at 70-120°C until completely dissolved to obtain a polyvinyl alcohol solution. After the solution is cooled, glucose oxidase and MnO2 nanoparticles are added in an ice bath and stirred to obtain a PVA-GOx-MnO2 hydrogel precursor solution. (2) Preparation of difatty acid phase change material: lauric acid and stearic acid were mixed, stirred evenly under heating conditions of 80-120°C, and then cooled, ground, and dried in sequence to obtain difatty acid phase change material; (3) Preparing a spinning solution: adding polyacrylonitrile, the difatty acid phase change material obtained in step (2), and the angiogenesis-promoting drug to N,N-dimethylformamide in sequence, stirring evenly, and obtaining a spinning solution; (4) Preparing a thermosensitive micro-nanofiber membrane loaded with angiogenic drugs: electrospinning the spinning solution obtained in step (3) to obtain a thermosensitive micro-nanofiber membrane loaded with angiogenic drugs; (5) The PVA-GOx-MnO2 hydrogel precursor solution obtained in step (1) is injected into a mold, and the thermosensitive micro-nanofiber membrane loaded with angiogenic drugs obtained in step (4) is placed on the PVA-GOx-MnO2 hydrogel precursor solution or immersed in the PVA-GOx-MnO2 hydrogel precursor solution, and multiple freeze-thaw cycles are performed. After demolding, a composite dressing with temporal response and functional synergy is obtained.

5. The method for preparing a composite dressing with temporal response and functional synergy according to claim 4, characterized in that: In step (1), the degree of polymerization of polyvinyl alcohol is 1700±50, the degree of alcoholysis is 88~99.8%, and the concentration of the polyvinyl alcohol solution is 5~25wt%; the amount of glucose oxidase added to the PVA-GOx-MnO2 hydrogel precursor solution is 0.01~2wt%, and the amount of MnO2 nanoparticles added is 0.02~0.06wt%.

6. The method for preparing a composite dressing with temporal response and functional synergy according to claim 4, characterized in that: The particle size of the MnO2 nanoparticles in step (1) is 10-25 nm. The method for synthesizing the MnO2 nanoparticles is as follows: potassium permanganate and ascorbic acid are dissolved in deionized water to obtain a potassium permanganate solution and an ascorbic acid solution, and the ascorbic acid solution is added to the potassium permanganate solution under stirring conditions of 400-3000 r / min. After the reaction is completed, the mixture is centrifuged and washed multiple times, and then dried to obtain the MnO2 nanoparticles. The concentration of the potassium permanganate solution is 5-30 mg / mL, the concentration of the ascorbic acid solution is 5-35 mg / mL, and the volume ratio of the potassium permanganate solution to the ascorbic acid solution is 1-3:3-1; The reaction time is 0.5~6h.

7. The method for preparing a composite dressing with temporal response and functional synergy according to claim 4, characterized in that: In step (2), the mass ratio of lauric acid to stearic acid is 5-3:1-2, and the phase change temperature of the difatty acid phase change material is 38-50°C.

8. The method for preparing a composite dressing with temporal response and functional synergy according to claim 4, characterized in that: In the spinning solution of step (3), the concentration of polyacrylonitrile is 15-25 wt %, the concentration of the difatty acid phase change material is 5-15 wt %, and the concentration of the angiogenesis-promoting drug is 1-10 wt %.

9. The method for preparing a composite dressing with temporal response and functional synergy according to claim 4, characterized in that: The electrospinning process parameters in step (4) are: ambient temperature 20~40℃, relative humidity 20~60%, needle gauge 14~20G, voltage 8~20kV, receiving distance 10~20cm, spinning rate 0.1~2mL / h, and drum speed 100~200rpm.

10. Use of the composite dressing with temporal response and functional synergy according to claim 1 or 2, characterized in that: Used as a material for repairing chronic diabetic wounds.

Citation Information

Patent Citations

  • Supramolecular hydrogel based on natural plant components as well as preparation and application of supramolecular hydrogel

    CN117084970A

  • Multifunctional hydrogel as well as preparation method and application thereof

    CN117815438A

  • Sugarcane molasses extract, application of cane molasses extract in preparation of chronic wound healing medicine and hydrogel of cane molasses extract

    CN118717902A

  • Multifunctional hydrogel and application thereof

    CN119606872A

  • Double-response collagen-based conductive hydrogel, medicine and preparation and application methods of double-response collagen-based conductive hydrogel and medicine

    CN120025564A

Cited By

  • Bionic multi-layer dressing for chronic diabetic wound and preparation method of bionic multi-layer dressing

    CN121818985A